Tree Nitrogen Status and Leaf Canopy Position Influence Postharvest Nitrogen Accumulation and Efflux from Pear Leaves - Sanchez, Enrique Eduardo; Righetti, Timothy L. (American Society for Horticultural Science, 2020)
`Cornice' pear trees (Pyrus communis L.) were fertilized with ammonium nitrate depleted in “N in Spring 1987 and 1988. In Aug., Oct., and Nov. 1988, midleaves on current season shoots were sampled at three positions from the periphery to the center of the canopy. Total N/cm' of leaf area remained almost constant through October, even though percent N concentration declined as specific leaf weight (SLW) increased. Furthermore, there was no substantial net change in either labeled or unlabeled N in either treatment until senescence began in October. Peripheral leaves contained higher levels of both reserve and newly acquired N than did less-exposed leaves. Despite large differences in N/cm2 for October samples, by November leaves from both high (HN) and low N (LN) trees exported similar percentages of their total N. The average N export to storage tissues irrespective of tree N status was 71%, 61%, and 52% for peripheral, medium, and interior leaves, respectively. The export of N was influenced more by the leaf position in the plant canopy than the nutritional status of the tree.